2010
DOI: 10.1124/mol.110.066423
|View full text |Cite
|
Sign up to set email alerts
|

Blockade by Nanomolar Resveratrol of Quantal Catecholamine Release in Chromaffin Cells

Abstract: The cardiovascular protecting effects of resveratrol, an antioxidant polyphenol present in grapes and wine, have been attributed to its vasorelaxing effects and to its anti-inflammatory, antioxidant, and antiplatelet actions. Inhibition of adrenal catecholamine release has also been recently implicated in its cardioprotecting effects. Here, we have studied the effects of nanomolar concentrations of resveratrol on quantal single-vesicle catecholamine release in isolated bovine adrenal chromaffin cells. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…3B). As previously observed (12) in the present study, we also found that BCCs rarely exhibited spontaneous single exocytotic events; this made easier the analysis of the net responses elicited by 30K ϩ . Thus the net bulk secretion (the cumulative sum of the areas of all spikes produced within a DP, the so-called quantal content or Q amp ) and the total number of spikes, considerably differed at the Data are means Ϯ SE and were pooled and analyzed from the peak Ca 2ϩ current (ICa) obtained at Ϫ10 mV, shown in Fig.…”
Section: C162supporting
confidence: 86%
“…3B). As previously observed (12) in the present study, we also found that BCCs rarely exhibited spontaneous single exocytotic events; this made easier the analysis of the net responses elicited by 30K ϩ . Thus the net bulk secretion (the cumulative sum of the areas of all spikes produced within a DP, the so-called quantal content or Q amp ) and the total number of spikes, considerably differed at the Data are means Ϯ SE and were pooled and analyzed from the peak Ca 2ϩ current (ICa) obtained at Ϫ10 mV, shown in Fig.…”
Section: C162supporting
confidence: 86%
“…Bearing in mind that t-Resv has been reported to have beneficial effects in the cardiovascular system through a NO-dependent mechanism [52,53], and assuming that t-Resv exhibits similar behaviour in humans in vivo, we suggest that the endothelial NO release described here may be partially involved in these effects. However, it is important to note that the effects described in this study were obtained with concentrations of t-Resv considerably higher than those measured in human plasma after normal dietary intake [54,55]. This suggests that the potential beneficial effect of resveratrol on the vascular endothelium will not be achieved after its dietary consumption, such as a moderate wine intake, and that a pharmacological intervention could be necessary to reach higher plasma levels.…”
Section: Discussionmentioning
confidence: 67%
“…e hyporeactivity was confirmed by a significant increase in the EC50 coefficient value in the study group and by lower maximal pressure values. Fernandez-Morales et al observed similar effects at nanomolar concentrations of resveratrol [13]. Kline and Karpiński's [14] study showed that resveratrol also depends on nonreceptor vasorelaxant mechanisms.…”
Section: Discussionmentioning
confidence: 84%